The Authority of Government in Clearing Hatefull and Hostilities Electronic Information Based on Tribe, Relegion, Race and Intergroup - I Gede Yusa; Dewi Bunga; Deris Stiawan (International Journal of Electrical and Computer Engineering (IJECE), 2017)
The Act Number 19 of 2016 concerning the amendment of The Act Number 11 of 2008 concerning Information and Electronic Transaction governing the authority of government in clearing hateful and hostilities electronic information based on tribe, religion, race and intergroup. On the one hand, the government authority aims to protect the public interest and the integrity of the nation, but on the other hand, termination of access to information would restrict the right to freedom of opinion and the right to privacy of Internet users. This study was a normative legal research, which examined the basic authority for the government to shut down negative content in cyberspace. Legal materials were collected through library research. The analysis was conducted qualitatively. This study examined three issues, namely; spreading hatred and hostility in cyberspace, legality government to close the spreading hatred and hostility and electronic evidence in spreading hatred and hostility. Spreading hatred and hostility were criminal acts that used the Internet as facilities. Internet was used by extremists to disseminate his teachings, even being used to commit acts of terrorism (cyber terrorism). In maintaining the unity and integrity, then the government had the authority to shut down access to the unlawful electronic system. The closure should be accompanied by proof of electronic information that contains hatred and hostility based on tribe, religion, race and intergroup